A Study on Cases Involving Violence Against Women Among Divorce Suits Tried in the Family Court of Van Province Between 2005-2009 - Can, Muhammet; Erbaydar, Tuğrul; Edirne, Tamer; Ölçer, Sabahat (The Bulletin of Legal Medicine, 2010)
While violence against women is an important public health problem with its negative impacts over physical and emotional health of women alongside ruining their social statuses, it is also considered as a field of forensic medicine which covers the judicial and human rights aspects of the problem. In the present study, we aimed to determine cases involving violence against women committed by their husbands and identify their characteristics among divorce suits tried between 2005-2009 in Van province,. By reviewing the files and records of divorce cases in the court archive which had been finalized between 2005-2009, we found and analyzed 193 cases involving violence and determined the ones that ended with an order of protection for the abused. Among those 193 cases, mean value for age of women was 31,39 (+8,46), number of children was 2,07 (+1,82), and official duration of marriage was 9,27 years (+8,36 years). As the mean rate of forensic/medical report presence in the files involving violence was 19,2%, the rate of issuing protection order in coordinance with Law No. 4320 was found to increase at a steady pace each year and determined to exhibit a mean rate of 15,5%. Court records and medical reporting procedures should be standardized for divorce suits and all cases of domestic violence. Informing and instructing judges, attorneys, and lawyers along with amelioration of the coordination among courts, social services network, forensic medicine units, and hospital emergency departments, should contribute in more efficient execution of Law No. 4320. Key words: Family court, divorce, violence against women, domestic violence